Wulangreh in performance: Philology, the traditional art of pitutur, and Ccltural transmission in Magelang - Rozib Sulistiyo; Abdullah Idi; Endang Rochmiatun (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The growing marginalization of traditional textual knowledge in the face of rapid socio-cultural transformation has exposed critical limitations in conventional approaches that treat texts as static and self-contained artifacts. Addressing this gap, this study reconceptualizes Wulangreh as a dynamic cultural system sustained through the interaction of textual plurality, performative practice, and community-based transmission. The study aims to develop an integrated analytical framework that explains how these dimensions collectively shape the sustainability of living textual traditions. Employing a qualitative interpretivist design, the research combines philological analysis of seven manuscript variants with performance ethnography across three pitutur communities in Magelang, Indonesia, supported by in-depth interviews, structured observations, and document analysis. The findings reveal that the endurance of Wulangreh does not depend on preservation in fixed textual forms but emerges through continuous social enactment, where communities actively construct and negotiate meaning. Textual variation is shown to follow structured patterns that reflect distinct transmission lineages, while performative practices selectively reorganize textual elements in response to contextual, aesthetic, and social considerations. These processes demonstrate that variation and adaptation are not indicators of instability but constitute core mechanisms of cultural resilience. This study is among the first to empirically integrate philological and performative perspectives into a unified model of textual sustainability, thereby extending the theoretical framework of performative philology. By positioning Wulangreh within the global discourse on living traditions, the study provides a new conceptual foundation for understanding how cultural texts endure in dynamic social environments and offers actionable insights for sustaining community-based knowledge systems.